From Spinning Silk to Spreading Saliva: Mouthpart Remodeling in Manduca sexta (Lepidoptera: Sphingidae). Issue 6 (12th November 2019) - Mikó, István; Rahman, Sarthok Rasique; Jones, Anne C; Townley, Mark A; Gominho, Brandon; Paudel, Sulav; Stupski, S David; Hines, Heather M; Schilder, Rudolf J
Abstract: As a model organism, the tobacco hornworm Manduca sexta (Linnaeus 1763) has contributed much to our knowledge of developmental processes in insects, and major developmental changes between different larval instars are generally well understood. Second and later instars of M. sexta do not produce silk, and their spinneret and accessory labial glands (=Lyonet's glands), structures thought to be key players in silk production in other lepidopterans, are highly reduced. To our knowledge, mouthparts and labial gland morphology of the silk-producing first instar have never been described. In this study, we compared the mouthpart morphology and transcriptome profile of first and later instars of M. sexta to determine whether the loss of silk production correlates with changes in the structure of the spinneret and the labial glands, and with changes in expression of silk-related genes. We found that the first instar, unlike later instars, has a typical, silk-producing spinneret with a tube-like spigot and well developed Lyonet's glands. Moreover, three known silk protein genes are highly expressed in the first instar but exhibit little to no expression in the embryo or later instars. Thus, the changes in morphology and gene expression presented here, coinciding with changes in larval behavior from silk production to saliva spreading, further our understanding of the developmental processes underlying this transition in this model organism.